2019
DOI: 10.6004/jnccn.2019.0018
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Melanoma, Version 2.2019, NCCN Clinical Practice Guidelines in Oncology

Abstract: The NCCN Clinical Practice Guidelines in Oncology (NCCN Guidelines) for Cutaneous melanoma have been significantly revised over the past few years in response to emerging data on immune checkpoint inhibitor therapies and BRAF-targeted therapy. This article summarizes the data and rationale supporting extensive changes to the recommendations for systemic therapy as adjuvant treatment of resected disease and as treatment of unresectable or distant metastatic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
263
1
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 347 publications
(280 citation statements)
references
References 157 publications
(451 reference statements)
1
263
1
4
Order By: Relevance
“…This case highlights the need to test earlier in the disease course (e.g., in stage III melanoma) rather than waiting until the onset of metastatic disease and could potentially argue for testing of even localized (stage I–II) cancer. Current guidelines suggest testing when clinically actionable (e.g., when therapies including clinical trials are available) ; however, these cases suggest that an ongoing discussion is warranted regarding the timing of genomic testing.…”
Section: Discussionmentioning
confidence: 99%
“…This case highlights the need to test earlier in the disease course (e.g., in stage III melanoma) rather than waiting until the onset of metastatic disease and could potentially argue for testing of even localized (stage I–II) cancer. Current guidelines suggest testing when clinically actionable (e.g., when therapies including clinical trials are available) ; however, these cases suggest that an ongoing discussion is warranted regarding the timing of genomic testing.…”
Section: Discussionmentioning
confidence: 99%
“…The crucial importance of regional nodal metastasis for prognostication, disease recurrence, and survival in melanoma is well supported with prospective data reflected by The American Joint Committee on Cancer (AJCC) staging and the National Comprehensive Cancer Network (NCCN) treatment guidelines . Sentinel lymph node biopsy (SLNB) is recommended for cN0 T2–T4 and select T1b melanomas, and until recently immediate completion lymph‐node dissection (iCLND) was recommended following all positive SLNBs .…”
Section: Introductionmentioning
confidence: 99%
“…The crucial importance of regional nodal metastasis for prognostication, disease recurrence, and survival in melanoma is well supported with prospective data reflected by The American Joint Committee on Cancer (AJCC) staging and the National Comprehensive Cancer Network (NCCN) treatment guidelines . Sentinel lymph node biopsy (SLNB) is recommended for cN0 T2–T4 and select T1b melanomas, and until recently immediate completion lymph‐node dissection (iCLND) was recommended following all positive SLNBs . The initial Multicenter Selective Lymphadenectomy Trial (MSLT‐I) demonstrated that SLNB followed by iCLND among patients with regionally metastatic melanoma confers prolonged disease‐free survival (DFS) and melanoma‐specific survival (MSS) over observation .…”
Section: Introductionmentioning
confidence: 99%
“…2 Current guidelines recommend dermatologic surveillance in patients with good response, nonetheless good response is not clearly specified and timing and frequency are not stated. [3][4][5] This study aimed to specify the need for routine skin examination in patients with durable response to TT and IT.…”
mentioning
confidence: 99%
“…Rivaroxaban, a direct factor Xa inhibitor, has demonstrated good effects in LV. 1,3,4 Compared to other treatments such as classic anticoagulants or intravenous immunoglobulin, rivaroxaban is way more convenient since it does not require injection, international normalized ratio monitoring or hospitalization.…”
mentioning
confidence: 99%